2020
DOI: 10.1044/2020_jslhr-20-00202
|View full text |Cite
|
Sign up to set email alerts
|

Taking Language Samples Home: Feasibility, Reliability, and Validity of Child Language Samples Conducted Remotely With Video Chat Versus In-Person

Abstract: Purpose There has been increased interest in using telepractice for involving more diverse children in research and clinical services, as well as when in-person assessment is challenging, such as during COVID-19. Little is known, however, about the feasibility, reliability, and validity of language samples when conducted via telepractice. Method Child language samples from parent–child play were recorded either in person in the laboratory or via video c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 31 publications
3
64
0
2
Order By: Relevance
“…For example, Aggarwal et al (2020) reported not only an increase in therapy services delivered remotely in India immediate after the COVID-19 pandemic but also acceptance and predicted future use. Speech-language pathologists who previously used telehealth understood its potential to provide access to clients in a larger geographical area and not predominantly clients who lived in rural areas (Manning et al, 2020;Sutherland et al, 2016). The pandemic enabled a diverse group of pediatric speech-language pathologists to finally experience this utility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Aggarwal et al (2020) reported not only an increase in therapy services delivered remotely in India immediate after the COVID-19 pandemic but also acceptance and predicted future use. Speech-language pathologists who previously used telehealth understood its potential to provide access to clients in a larger geographical area and not predominantly clients who lived in rural areas (Manning et al, 2020;Sutherland et al, 2016). The pandemic enabled a diverse group of pediatric speech-language pathologists to finally experience this utility.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have collected information about the use of and the attitudes toward telehealth in the provision of pediatric speech-language services, most of these data were collected prior to the COVID-19 pandemic (Manning et al, 2020;Orlando et al, 2019). Prior to March 2020, telehealth research was limited due to the prolific barriers and restrictions creating underutilization of this delivery method within the pediatric population.…”
mentioning
confidence: 99%
“…Before posing our questions, it is important to point out that the testing modes are different between the two samples by necessity: one group was tested in person, the other remotely via video chat. However, emerging evidence suggests that the two testing modes are largely comparable in terms of child engagement, speech intelligibility, amount and characteristics of language elicited, and reliability of transcription and scoring ( Waite et al, 2010 ; Ciccia et al, 2011 ; Sutherland et al, 2017 ; Manning et al, 2020 ). It is also important to point out that the current comparisons are cross-sectional rather than longitudinal.…”
Section: Introductionmentioning
confidence: 99%
“…Various stages of research such as participant recruitment (Amon, Campbell, Hawke, & Steinbeck, 2014;Gilligan, Kypri, & Bourke, 2014;Thornton, Batterham, Fassnacht, Kay-Lambkin, Calear, & Hunt, a Boğaziçi University, Department of Psychology, gunes.oner@boun.edu.tr, ORCID: 0000-0002-0312-6712 b Boğaziçi University, Department of Psychology, neslihan.oguz@boun.edu.tr, ORCID: 0000-0003-4980-0108 c Boğaziçi University, Department of Psychology, ozdes.cetin@boun.edu.tr, ORCID: 0000-0001-5007-1411 d Boğaziçi University, Department of Psychology, simge.ersonmez@boun.edu.tr, ORCID: 0000-0001-9212-1333 e Boğaziçi University, Department of Psychology, pinar.karan@boun.edu.tr, ORCID: 0000-0001-9895-0175 f Boğaziçi University, Department of Psychology, mahmut.kurupinar@boun.edu.tr, ORCID: 0000-0001-5376-1303 g Boğaziçi University, Department of Psychology, oya.serbest@boun.edu.tr, ORCID: 0000-0001-7442-4699 h Corresponding author: Boğaziçi University, Department of Psychology, gaye.soley@boun.edu.tr, ORCID: 0000-0002-6333-6017 2016), testing (e.g., Discoveries Online [Rhodes et al, 2020]; Lookit ; TheChildLab.com [Sheskin & Keil, 2018]), coding (Chouinard, Scott, & Cusack, 2019) and sharing the materials and data (e.g., the OSF [Foster & Deardorff, 2017], The Child Language Data Exchange System -CHILDES [MacWhinney, 2000]; databrary.org [Adolph, Gilmore, & Kennedy, 2017]) have increasingly moved to online platforms. While remote data collection has long been in place for other fields of psychology, developmental scientists started adopting online methods for data collection only in recent years (e.g., Chouinard et al, 2019;Chuey, Lockhart, Sheskin, & Keil, 2020;Johnston, Sheskin, & Keil, 2019;Kominsky, Gerstenberg, Pelz, Sheskin, Singmann, Schulz, & Keil, 2021;Leshin, Leslie, & Rhodes, 2020;Manning, Harpole, Harriott, Postolowicz, & Norton, 2020;Nussenbaum, Scheuplein, Phaneuf, Evans, & Hartley, 2020;Richardson, Sheskin, & Keil, 2021;Scott, Chu, & Shulz, 2017;Smith-Flores, Perez, Zhang, & Feigenson, 2021;Soley & Köseler, 2021;Tran, Cabral, Patel, & Cusack, 2017). COVID-19 pandemic conditions have further spread the use of online research tools in many fields, including developmental science.…”
Section: Online Developmental Research: Observations From Moderated Studiesmentioning
confidence: 99%
“…For instance, studies done with children include short tasks (10-to-20 minutes) such as showing children animations and asking them questions about these (e.g., Chuey et al, 2020;Leshin et al, 2020) as well as longer tasks (e.g., 30-to-60 minutes) that require children to exhibit sustained concentration in order to make several repeated decisions (Nussenbaum et al, 2020). Online platforms are also used to collect language samples (Manning et al, 2020) and looking time data from infants (e.g., Smith-Flores et al, 2021). Importantly, through both moderated and unmoderated online studies, researchers seem to be able to collect data that are comparable to data from lab-based studies (e.g., Manning et al, 2020;Nussenbaum et al, 2020;Rhodes et al, 2020;Sheskin & Keil, 2018;Smith-Flores et al, 2021;Soley & Köseler, 2021), providing preliminary evidence about the reliability of these methods.…”
Section: Online Developmental Research: Observations From Moderated Studiesmentioning
confidence: 99%